Gender-Specific Application Behavior, Matching, and the Residual Gender Earnings Gap - Benjamin Lochner; Christian Merkl (Institute of Labor Economics (IZA), 2023)
This paper analyzes the relationship between gender-specific application behavior, employer-side flexibility requirements, and the gender earnings gap using a unique combination of the German Job Vacancy Survey (JVS) linked to administrative employment records. We document that women have a substantially lower probability of applying to jobs with high flexibility requirements at high-wage firms than do men but have the same probability of being hired upon application. In our two-stage search model, these empirical patterns are rationalized by firms compensating workers for meeting employer-side flexibility requirements. Consistently, we empirically show that among women, mothers face the largest earnings discounts relative to men in jobs with high flexibility requirements.
Keywords: E24; J16; J31; 330; job search; application behavior; gender earnings gap